Dark and Singular Optical Solitons for Kundu-Eckhaus Equation with Differential Group Delay by the Generalized ϕ6-Model Expansion (Contemporary Mathematics, 2025)
This paper recovers optical solitons solutions with polarization-mode dispersion in optical fibers. The governing model is the Kundu-Eckhaus equation. The adopted integration scheme is the generalized ϕ6-model expansion. The intermediary functions are the Jacobi’s elliptic functions and the Weierstrass’ elliptic functions. The parameter constraints for the existence of such solitons are also presented.
Keywords: solitons, integrability